2015
DOI: 10.1186/s13731-015-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

User innovation and entrepreneurship: case studies from rural India

Abstract: Innovation research has abundant literature on technologically advanced innovations and entrepreneurship. However, literature from a rural innovator and entrepreneur perspective is sparse. Therefore, we explore rural user innovation and entrepreneurship in a developing country, India. Using multiple case study research method, we study cases of five rural user innovations in detail. These rural innovators innovated to alleviate the drudgery of their lives and to fulfill their need for a low-cost local solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Other studies focused on a particular market circumstances in which classical producer innovation could be lacking [38,39] or disenchantment and disinterest among consumers is the reason for slow market diffusion [5]. In these situations, users commonly start to innovate for themselves because local needs are not satisfied by the market [40,41].…”
Section: User Innovation In Complex Technologiesmentioning
confidence: 99%
“…Other studies focused on a particular market circumstances in which classical producer innovation could be lacking [38,39] or disenchantment and disinterest among consumers is the reason for slow market diffusion [5]. In these situations, users commonly start to innovate for themselves because local needs are not satisfied by the market [40,41].…”
Section: User Innovation In Complex Technologiesmentioning
confidence: 99%
“…Research studies have been so far conducted in India mostly used case studies or storytelling approach. They were more focused toward the concept of social innovation through incubators and government initiatives (Sonne 2012) and towards cases of social entrepreneurs with the mission of rural development (Yadav and Goyal 2015). Selective research studies conducted in India in the field of social entrepreneurship are shown in Table 1.…”
Section: Development Of Social Entrepreneurship In Indiamentioning
confidence: 99%
“…This brings us to identify other growth spots for necessity-based entrepreneurs through external support from extended family, community and mentor networks. Yadav and Goyal (2015) in their study point out that the commercialization of a product is more likely to occur with the help of enabling factors, such as individuals like friends and family and external institutions such as the government and nongovernment organizations, educational institutions, and private sector organizations.…”
Section: Growth Drivers For Necessity-based Women Entrepreneursmentioning
confidence: 99%